The impact of Malay language proficiency, summative assessment, parental support, and activities outside of teaching time on students' moral development in Malaysian secondary schools: A conceptual review - Gurumoorthy Poobalan; Roslee Talip; Junaidi Asman; Rosna Padan; Sukuneswari Kaliappan; Syd Alimulhakim Bin Syd Ali; Aishah Binti Mohd Aris (Global Scientific and Academic Research, 2024)
In the 5.0 society, moral education in the classroom is crucial for shaping students' personalities, fostering mutual understanding and collaboration, and ultimately bringing the community closer together in the pursuit of a more civilized society. Improving students' performance in Moral Education only based on their test scores does not reflect the quality of their moral growth. There is a strong emphasis on classroom assessment in moral education, but children' moral development is impacted by more than just that. Consequently, the primary necessity for research into the field of Moral Education is to conduct thorough evaluations in order to produce a new generation of morally upright citizens. The purpose of this research is to determine how language skills, summative assessments, parental involvement, and activities outside of teaching time affect students' moral development in Malaysian secondary schools. Researchers have utilized library review as a means to gather the essential information. The study discovered that the comprehensive moral development of secondary school pupils in Malaysia is influenced by their proficiency in the Malay language, the use of effective evaluation methods, parental engagement, and participation in extracurricular activities. This study's findings can help educators, particularly those responsible for developing and evaluating moral education curricula, to focus on areas beyond classroom assessment that have the greatest impact on students' moral development and character.